2004
DOI: 10.3758/bf03196891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetition and response deadline on associative recognition in young and older adults

Abstract: The present study examined the joint effects of repetition and response deadline on associative recognition in older adults. Young and older adults studied lists of unrelated word pairs, half presented once (weak pairs) and half presented four times (strong pairs). Test lists contained old (intact) pairs, pairs consisting of old words that had been studied with other partners (rearranged lures), and unstudied pairs (new lures), and participants were asked to respond "old" only to intact pairs. In Experiment 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
152
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(184 citation statements)
references
References 106 publications
30
152
2
Order By: Relevance
“…The present results provide support for the associative deficit hypothesis in older adults (e.g., Castel, 2007;Castel & Craik, 2003;Light et al, 2004;Naveh-Benjamin, 2000;Naveh-Benjamin, Guez, Klib, & Reedy, 2004;Naveh-Benjamin, Guez, & Shulman, 2004) and extends this concept to nonverbal, face materials. We 4 We also analyzed discriminability with face age entered as a factor.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results provide support for the associative deficit hypothesis in older adults (e.g., Castel, 2007;Castel & Craik, 2003;Light et al, 2004;Naveh-Benjamin, 2000;Naveh-Benjamin, Guez, Klib, & Reedy, 2004;Naveh-Benjamin, Guez, & Shulman, 2004) and extends this concept to nonverbal, face materials. We 4 We also analyzed discriminability with face age entered as a factor.…”
Section: Discussionsupporting
confidence: 83%
“…This suggests that younger adults would be able to offset the effects of increased familiarity by means of recollection and would exhibit fewer false alarms to conjunctions of repeated items. Light et al (2004) reported data consistent with this prediction. In particular, those researchers had older and younger adults study word pairs presented one time or four times.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Instead, as suggested by TCM coupled with the associative deficit hypothesis, the younger adults' propensity to make a larger proportion of backward and remote intrusions to double-function pairs may be a natural consequence of intact item-context binding. The hypothesis that older adults are particularly impaired at item-context binding is also supported by evidence arguing for a greater effect of aging on recollection than on familiarity in recognition memory (Healy et al, 2005;Howard, Bessette-Symons, Zhang, & Hoyer, 2006;Light et al, 2004;Prull et al, 2006).Although older adults made disproportionately fewer associative intrusions than younger adults, this deficit was not due to an inability to generate responses. Consistent with previous findings, the older adults made more incorrect recalls (intrusions) than the younger adults (Kliegl & Lindenberger, 1993;Zacks, Radvansky, & Hasher, 1996;Balota et al, 1999; NavehBenjamin, 2000;Kahana et al, 2002Kahana et al, , 2005.…”
mentioning
confidence: 92%
“…There is overwhelming evidence that WM capacity decreases at a steady rate from about 20 years of age onwards (Brockmole & Logie, 2013;Salthouse & Babcock, 1991), and that this decline is greater for bindings than for item information (Cowan, Naveh-Benjamin, Kilb, & Saults, 2006;Peterson & Naveh-Benjamin, 2016. A large array of varied findings from item and associative recognition also indicates that the underlying cause of most age-related memory impairments is a decreased ability to form novel bindings (Ahmad, Fernandes, & Hockley, 2015;Buchler et al, 2011;Chalfonte & Johnson, 1996;Light, Patterson, Chung, & Healy, 2004). Our model suggests a causal link between the correlated decline in WM capacity and binding ability with age -forming new bindings requires WM resources and the decrease in WM capacity is responsible for the reduced ability to establish and store such bindings (Buchler et al, 2011).…”
Section: Binding Problems In Old Agementioning
confidence: 99%